(untitled) (XXI Century. Spanish Literature and Culture, 2017)
In Jose Maria Merino´s fiction, there are some fantasy, marvelous (alongside the legendary and the mythical), science-fiction and, to a lesser extent, realism elements present. However, the best term to define his work that of “fragile reality”. It is very common for him to use motifs such as the double, the apocryphal or metafiction. With them, he adds a diverting touch to his work and places the reader in a world where it is difficult to distinguish the line between what is real and what is fiction. Here, we will analyse three novels essential for understanding such a concept. These novels are the following: Novela de Andrés Choz (1976), La orilla oscura (1985) and Los invisibles (2000). The analysis of the elements in these novels will let us understand better the way Jose Maria Merino´s fictional world is built.